Relationship between language anxiety, oral performance and written English performance among secondary school students - Rosnah Mohd. Sham
The issue of students' poor performance in the English language particularly compared to other languages is an important issue because English is one of the most important languages of the world, and it is the second language in Malaysia. Usually, the students experience language anxiety when they have limited exposure and usage of the English language. Many studies indicated that most teachers were not satisfied with their students' language competence. The study aims to investigate the relationship between language anxiety, oral performance, and written English performance among secondary school students. A quantitative approach was used in this study with one semi-structured interview study question as an additional question. Data collection for the quantitative approach was conducted by using questionnaires to 11 Secondary schools from Putrajaya Federal Territory. Meanwhile, data collection for additional study question was conducted by conducting a semi-structured interview with four English teachers. The Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire was used to collect data in terms of Communication Apprehension (CA), Test Anxiety (TA) and Fear of Negative Evaluation (FNE). Statistical Package for the Social Sciences version 22 was used to analyse the quantitative data. Data from semi-structured interviews were analyzed with directed and conventional content analyses. Based on the quantitative analysis, the majority of the secondary school students obtained good in oral performance and scored A- in average in written English performance. Majority of students had a low level of language anxiety in terms of CA, T A and FNE. The study found no significant difference in terms of CA, TA and FNE between male and female students. There was a significant, inversed and weak relationship between the language anxiety in terms of CA and TA and oral performance of the students. However, there was no significant relationship between FNE and oral performance. There was also a significant, inversed and weak relationship between the language anxiety in terms of CA, TA and FNE and written English performance of the students. From the semi structured interviews, this study found that for oral performance, the students had prepared and practised the topics with guidance from the English teachers. In fact, they had memorized the scripts. However, this helped the students a lot in oral performance. Students who obtained excellent and good in oral performance also obtained A+, A and A- in written English performance. The significant, inversed and weak relationship between language anxiety and English language performance indicated that students with high English performance experienced a low level of language anxiety. The insignificant difference in terms of CA, TA and FNE between male and female students enables the teachers to plan strategies to overcome the language anxiety. The study provided evidence that language anxiety influences students' English performance without gender disparity. These findings suggested further research to find the effect of language anxiety towards students' English performance in other schools such as international and boarding schools.